The compromises of rewilding - Rouet-Leduc, Julia (2017)
The purpose of this thesis is to explore how rewilding has emerged as a new alternative to classic nature conservation to reconcile humans with wild nature. The study will explore what are the compromises required for rewilding in a Swedish context. It will focus on the expectations and the processes leading to the rewilding projects and how human expectations for landscapes, animals and nature have to compromise. Most of our modern landscapes being tamed and domesticated, they correspond more to an idea of beautiful, in opposition with the sublime which can designate the wilderness, which is, in Kant’s terms, untamed, wild, and sometimes ugly and terrifying. If Kant considers that the only way for humans to enjoy this sublime nature is pure disinterest, we will look at how rewilding can be a way to restore autonomy and ecological integrity to ecosystems while offering to humans an experience of the sublime nature and letting them benefit from it. This paper will look at Rewilding Lapland as a case study, it proposes to rewild a large area in Northern Sweden by supporting some keystone species like the beaver and restoring key areas of the landscape like rivers and grazing lands. The stated aim of this Rewilding Lapland is to develop a naturebased economy where entrepreneurship and economical activities are combined with nature conservation. Thus, public awareness, local communities approval and nature-based economies around rewilding will be studied as compromises between nature and people.